Defining 'research inspired teaching' and introducing a research inspired online/offline teaching (riot) framework for fostering it using a co-creation approach. (January 2022) - Pezaro, Sally; Jenkins, Martin; Bollard, Martin
Abstract: Background: There are calls to ensure that evidence-based practice is enabled for every midwife and nurse by means of education, research, leadership and access to evidence. Concurrently, there is a global call for universities to foster 'Research Inspired Teaching'. Yet such teaching must first be defined and may usefully be developed, delivered, and evaluated as part of a framework approach. Objective: To co-create a uniform definition of 'Research Inspired Teaching' and a framework for developing, delivering, and evaluating it. Design: A co-creation approach was taken, underpinned by the interpretive framework of communal constructivism. Setting: United Kingdom. Participants: The sampling strategy was purposive, whereby those who had reportedly actively engaged in 'Research Inspired Teaching' were invited to participate. The resulting multidisciplinary team of co-creators ( n  = 14) included students, educators, and self-identified facilitators of 'Research Inspired Teaching'. Methods: The co-creation of outputs was facilitated by two online co-creation workshops. All creative, written, and verbal contributions made by co-creators were collected as data and used to 'co-define', 'co-design' and 'co-refine' outputs. To enhance credibility, triangulation was used throughout. A final review of results presented in this article via all co-creators concluded this process. Results: This article presents a definition of teaching, a definition of research, a founding definition of Research Inspired Teaching and a guiding framework along with 10 core principles for developing, delivering, and evaluating it. Conclusions: These outputs may be useful for both midwifery and nursing faculties, providing common language for collaboration and inspiring further developments and research. In pursuit of excellence, further international research could usefully investigate how these outputs may further bridge the Research-Teaching Nexus in Higher Education, and partner with other universities looking to cultivate, evidence and promote their own 'Research Inspired Teaching' in practice. In this pursuit, inter-university partnerships would be welcomed. Highlights: There is a global call to foster 'Research Inspired Teaching' (RIT). The teaching–research nexus in practice can be complex. Definitions of 'Teaching', 'Research' and 'RIT' were co-created. A guiding Research Inspired Online/Offline Teaching (RIOT) Framework was co-created.